1993
DOI: 10.2307/3431398
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Studies of the Association between Demands for Hospital Services and Air Pollution

Abstract: Studies of the associations between air pollution and hospital admissions and emergency room use are reviewed, including studies of air pollution episodes, time-series analyses, and cross-sectional analyses. These studies encompass a variety of methods of analysis and levels of air quality. Findings from all three types of studies were generally consistent in that almost all of the studies reviewed found statistically significant associations between hospital use and air pollution; this unanimity may have resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Important potential confounding factors that may bias time series studies of air pollution and mortality (or morbidity) are factors which vary on shorter timescales like calendar specific days, such as day of the week and holiday indicator (Lipfert, 1993). These trends are not necessarily present, but they occur often enough that they should be checked (Samoli et al, 2011;Schwartz et al, 1996).…”
Section: Day Of the Week And Holiday Indicatormentioning
confidence: 99%
See 3 more Smart Citations
“…Important potential confounding factors that may bias time series studies of air pollution and mortality (or morbidity) are factors which vary on shorter timescales like calendar specific days, such as day of the week and holiday indicator (Lipfert, 1993). These trends are not necessarily present, but they occur often enough that they should be checked (Samoli et al, 2011;Schwartz et al, 1996).…”
Section: Day Of the Week And Holiday Indicatormentioning
confidence: 99%
“…The GLM with Poisson regression has been widely applied in epidemiological studies of air pollution (Dockery & Pope III, 1994;Dominici et al, 2002;Lipfert, 1993;Metzger et al, 2004;Tadano et al, 2009) but it needs caution, as sometimes this model may not fit well to the database. There are two statistical methods that can be used to evaluate goodness of fit in GLMs, as follows.…”
Section: Goodness Of Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1980s, many studies showed an increase in hospital admissions due to asthma associated with O 3 and particles exposure in adults, children, and the elderly. Most of these studies were conducted in the USA 19 . They all described the health effects at concentrations below the North American air quality standards.…”
Section: Asthma Exacerbationsmentioning
confidence: 99%